A Review of Internal and Governance Factors on Tax Avoidance (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study seeks to evaluate the extent to which profitability, leverage, independent commissioners, and political links influence tax avoidance in Indonesian mining companies for the 2021–2024 timeframe. The mining sector was chosen because it contributes significantly to national income but is typically associated with the practice of tax avoidance. The novelty of this study lies in the addition of the political connections variable, which has rarely been studied in the context of Indonesian mining. The research data were obtained from annual reports and financial statements of companies obtained through purposive sampling, resulting in 77 observations. Multiple linear regression analysis under a quantitative method was applied, and the evidence suggests that profitability contributes positively to tax avoidance, as higher profits are associated with a stronger tendency for companies to minimize tax payments. Conversely, political connections have a negative effect, indicating that political and military experience shapes loyalty to the interests of the state, thereby encouraging tax compliance. Meanwhile, leverage and independent commissioners do not exert any influence on tax avoidance. The outcomes of this research may serve as a reference for regulators, scholars, and investors to better comprehend the determinants of tax avoidance and to contribute to enhancing governance structures and refining tax policy.